PENGARUH PEMAHAMAN PERATURAN PAJAK DAN PELAYANAN APARAT PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PREFERENSI RISIKO SEBAGAI VARIABEL MODERASI (Studi Kasus Pada UMKM yang terdaftar di KPP Pratama Demak) - Suntono .; Andi Kartika (Dinamika Akuntansi Keuangan dan Perbankan, 2015)
The purpose of this study re-write the understanding of the tax laws and officials tax service on taxpayer compliance with risk prefernces as a moderating variable. The population in this research in taxpayer MSMEs listed in KPP Pratama Demak. The sampling tehnique was convenience sampling method which produced a sample of 88 MSMEs. The analysis methode that used in study is a multiple linier regression analysis. The results showed that an understanding of the tax law and officials tax service have positif significant effect on taxpayer compliance MSMEs partially in Demak residence. The risk preferences cannot the relationship between the understanding of the tax laws with tax compliance and the relationship between officials tax service with tax compliance. Keywords: the understanding of the tax laws, officials tax service, taxpayer compliance, risk preferences